2010
DOI: 10.1080/09687761003657572
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation across time of first-generation online learners

Abstract: Self-regulatory skills have been associated with positive outcomes for learners. In the current study, we examined the self-regulatory skills of students who are firstgeneration online learners over the course of their first semester of online instruction. The purpose of this study is to determine whether the online selfregulatory skills of learners changed across time as associated with being immersed in their first online learning environment. The results of the current study indicate no significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 0 publications
3
32
0
1
Order By: Relevance
“…According to Barnard et al [36], students who lack the ability to self-regulate their studies are limiting their opportunity of enhancing their self-directed learning paths and reduce their chances of benefiting from the course resources effectively in order to achieve a better academic performance. Selfregulatory learning in brief has been seen to be the ability of exercising autonomous control over one's learning behaviour and environment [6,39]. Our results indicated that the students' perceptions of self-regulated learning are unique to individual students.…”
Section: Discussion and Further Worksupporting
confidence: 49%
“…According to Barnard et al [36], students who lack the ability to self-regulate their studies are limiting their opportunity of enhancing their self-directed learning paths and reduce their chances of benefiting from the course resources effectively in order to achieve a better academic performance. Selfregulatory learning in brief has been seen to be the ability of exercising autonomous control over one's learning behaviour and environment [6,39]. Our results indicated that the students' perceptions of self-regulated learning are unique to individual students.…”
Section: Discussion and Further Worksupporting
confidence: 49%
“…Secondly, students who are self-efficacious in their self-regulated learning do not necessarily adopt mastery goals, which focus on mastery and understanding of content rather than performance (Ferla, Valcke, & Schuyten, 2010). Students may not necessarily use appropriate SRLS given their academic needs, and the strategies used are not likely to improve while enrolled in online courses (Barnard-Brak, Paton, & Lan, 2010). Therefore, faculty should not expect students to become better self-regulated learners simply from increased exposure to or experience with online courses.…”
Section: Why Promote Self-regulated Learning Strategies (Srls) In Onlmentioning
confidence: 99%
“…Empirical research has shown that implementing various strategies in online courses can foster SRLS in students, and that structuring of the online learning environment to promote self-regulated learning is a central component of driving successful student usage of SRLS (Barnard-Brak et al, 2010;Ferla et al, 2010;Zimmerman, 1989). Researchers have suggested that SRLS are of greater importance in online learning environments due to their more autonomous nature (Dabbagh & Kitsantas, 2004).…”
Section: Why Promote Self-regulated Learning Strategies (Srls) In Onlmentioning
confidence: 99%
“…Several researchers have indicated the presence and importance of self-regulated learning in online learning environments (Barnard, Lan, To, Paton, & Lai, 2009;Nicol, 2009;Paraskeva, Mysirlaki, & Choustoulakis, 2009). Research studies (Artino, 2008;Artino & Stephens, 2009;Barnard-Brak, Paton, & Lan, 2010;Hodges & Kim, 2010;Matuga, 2009;Shea & Bidjerano, 2010) have shown that online learning is highly student-centered, where they have to assume more responsibilities and autonomy, especially in asynchronous learning environments. For example, the more self-regulatory skills students possess, the more likely they are to be successful in online learning environments (Shea & Bidjerano, 2010).…”
Section: Self-regulated Learning and Online Educationmentioning
confidence: 99%